2013
DOI: 10.1103/physrevlett.110.240501
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Implementation of Assisted Quantum Adiabatic Passage in a Single Spin

Abstract: Quantum adiabatic passages can be greatly accelerated by a suitable control field, called a counter-diabatic field, which varies during the scan through resonance. Here, we implement this technique on the electron spin of a single nitrogen-vacancy center in diamond. We demonstrate two versions of this scheme. The first follows closely the procedure originally proposed by Demirplak and Rice [J. Phys. Chem. A 107, 9937 (2003)]. In the second scheme, we use a control field whose amplitude is constant but whose ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
177
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(177 citation statements)
references
References 53 publications
(57 reference statements)
0
177
0
Order By: Relevance
“…The shortcuts to adiabaticity are based on the preparation of the controlled system into eigenstates of the Hamiltonian invariants, that characterise all the transformations of the given Hamitonian. The superadiabatic protocols were recently tested on two-level systems, an energy level anticrossing for a Bose-Einstein condensate loaded into an optical lattice [7][8][9] and the magnetic resonance of a one-half spin [10]. Those experiments demonstrated that superadiabatic protocols realize quantum fidelity equal to one, speed close to the quantum limit, and robustness against parameter variations, making them useful for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The shortcuts to adiabaticity are based on the preparation of the controlled system into eigenstates of the Hamiltonian invariants, that characterise all the transformations of the given Hamitonian. The superadiabatic protocols were recently tested on two-level systems, an energy level anticrossing for a Bose-Einstein condensate loaded into an optical lattice [7][8][9] and the magnetic resonance of a one-half spin [10]. Those experiments demonstrated that superadiabatic protocols realize quantum fidelity equal to one, speed close to the quantum limit, and robustness against parameter variations, making them useful for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…(12),Ω R is calculated from Eqs. (15) or (16). However, the consistency condition is generally not satisfied, i.e.,φ = ϕ = ω L t. For the Allen-Eberly protocol [11],…”
Section: The Counterdiabatic Methodsmentioning
confidence: 99%
“…In this paper we focus on speeding up "rapid adiabatic passage" (RAP) population inversion processes in two-level systems [10,15,16], beyond the RWA. Without the RWA, a consistency condition between the diagonal and the non-diagonal elements of the interactionpicture Hamiltonian, which involves the phase ϕ(t) of the field and its derivative with respect to time,φ(t), must be satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques are generally referred to as "shortcuts to adiabaticity" (STA), and involve modifying control fields to suppress the net effect of non-adiabatic errors [20][21][22][23][24][25]. Recent experiments have successfully implemented versions of these strategies [26][27][28][29][30].…”
mentioning
confidence: 99%
“…These techniques are generally referred to as "shortcuts to adiabaticity" (STA), and involve modifying control fields to suppress the net effect of non-adiabatic errors [20][21][22][23][24][25]. Recent experiments have successfully implemented versions of these strategies [26][27][28][29][30].A key drawback of the transitionless driving strategy and its higher order variants [20][21][22][23][24][25] is that they require the exact diagonalization of a time-dependent Hamiltonian, making them unwieldy for systems with many degrees of freedom. They are thus unsuitable for an important class of quantum state transfer problems, where the goal is to transfer an initial state in a localized system having discrete energy levels to a propagating state in a continuum such as a waveguide or a transmission line (see, e.g., [31][32][33]).…”
mentioning
confidence: 99%